Facile synthesis of 2, 5-bis(silyl)selenophene-1, 1-dioxide and its photophysical properties. (2nd September 2016) - Masuda, Toshiyuki; Inagaki, Yusuke; Momma, Hiroyuki; Kwon, Eunsang; Setaka, Wataru
Abstract : The reaction of 2, 5-bis(silyl)thiophenes with m CPBA gave the corresponding 1, 1-dioxides in good yields. The kinetics of the reactions and structures were discussed. Abstract : 2, 5-Bis(trimethylsilyl)selenophene-1, 1-dioxide was easily synthesized in 80% yield by reaction of selenophene with the common oxidant m -chloroperbenzoic acid ( m CPBA). The oxidation proceeded as a typical consecutive reaction. The kinetic study revealed that the rate of the first oxidation is faster than that of the second oxidation. The structure of the dioxide was identified by NMR spectroscopy and X-ray crystallography. The structural parameters of the dioxide show lower aromaticity as compared with that of selenophene. The HOMO–LUMO transition of the dioxide is remarkably red-shifted as compared with that of selenophene, because of the interactions between the π-orbitals of the ring and the p-orbitals of the oxygen atoms. A dichloromethane solution of the dioxide showed weak fluorescence due to the heavy-atom effect.